Learning Challenges and Perceptions Toward Audiobook-Based English Learning at SLB Negeri 1 Tabanan - Ariastini, Ida Ayu Ketut; Kusuma, I Putu Indra; Pratiwi, Ni Putu Astiti; Ana, I Ketut Trika Adi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
English learning for visually impaired students still faces various challenges, particularly due to the limited availability of learning media suited to their needs. This study aims to analyze the challenges and perceptions of teachers and visually impaired students toward the use of audiobooks in English learning at SLB Negeri 1 Tabanan. This research was designed as a qualitative study, with data collected through interviews. Then, Miles and Huberman’s theory is used in analysing data where data analysis consists of four parts: data collection, data reduction, data presentation, and conclusion drawing/verification. Researchers used interviews to collect data with one English teacher and four visually impaired students to obtain deeper insights into their learning challenges, experiences with existing media, and expectations of audiobook-based English learning. The study results are. First, teachers faced limitations in accessing and developing learning media, so they relied mainly on braille, WhatsApp voice notes, and the Merdeka Mengajar modules. Second, students experienced difficulties in using braille, felt bored with monotonous media, and required more varied and engaging audio-based resources. Third, both teachers and students expressed positive perceptions of audiobooks, considering them practical, flexible, and capable of enhancing learning motivation. They expected audiobooks with short duration, clear and expressive narration, bilingual content, and replayable features. The findings reinforce the importance of adopting inclusive, flexible, and learner-centered approaches in special education settings, particularly through the use of audiobooks.